Aluminium dross/soda lime glass waste-derived high-quality glass foam - Ahmed A.M. El-Amir (Elsevier, 2021)
This work introduces for the first time the use of waste aluminium dross obtained from the aluminium industry as a foaming agent to produce sustainable foam glasses from soda-lime glass powders derived from the lapping machine. The resulting foam briquettes (8ⅹ8ⅹ8 cm3) have a crack-free, 3-D cellular structure with closed pores whose geometries varied between elliptical-, pentagonal-, and hexagonal-shaped constructions. These glass foams demonstrate a lightweight (≥0.28 g/cm3), high CCS (≤12 MPa), low thermal conductivity (0.11–0.21 W/m-K), and contain more than ∼ 85 vol.% gas bubbles enclosed between 15 vol.% impervious glass walls. These properties are in line with the requirements of the international standard for commercial glass foams, revealing their strong capability to be used in potential applications in sustainable buildings and energy efficiency in the industry.